Monkey menace in Kwa Vonza/Yatta Ward, Kitui County, Kenya: Threat to food and nutrition security and sustainable livelihoods - Sylvester K Mutavi (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2022)
Since time immemorial, farmers in the arid and semi-arid lands in Kitui County have had many challenges in attaining food and nutrition security. This is largely attributed to inadequate rains, crop diseases, pests, and crop damage by wild animals among others factors. However, the monkey menace and its threats to food security and sustainable livelihoods in Kitui County are not documented. On this basis, a socio-economic survey was carried out in Kwa Vonza/Yatta ward, Kitui Rural constituency in Kitui County to establish i) the extent of damage by monkeys in the ecosystems ii) socio-economic impacts caused by monkeys iii) mitigation measures employed to control the monkey menace in Kitui rural constituency. The socio-economic survey, using one hundred and fifty (150) respondents, revealed that 65% of the respondents indicated that the monkey menace was a threat to food security, and human and livestock life. The respondents noted that monkeys damage their crops (cereals, fruits, and vegetables) on the farm, kill kids of goats and lambs of sheep, and damage food in stores and kitchens. In extreme cases of dry spells, 25% of the respondents indicated the monkeys caused physical injuries to children when the monkeys are looking for food in their homesteads. The respondents felt that the government, through Kenya wildlife services, should intervene to control the monkey population in the hilly habitats for the farmers to have gainful agricultural production and sustainable livelihoods.